C07 Skinner box test for strategy shifting impairments in BACHD rats. (29th August 2012) - Jansson, E; Massioui, NE; Doyère, V; Yo, L; Riess, O; Nguyen, HP
Abstract : Background: The BACHD rat is a novel animal model of Huntington disease expressing the full-length human huntingtin gene with 97 CAG/CAA repeats. We are investigating whether these rats are impaired during strategy shifts, as this is common among Huntington disease patients. We have previously found that BACHD rats are impaired during reversal learning in the simple swimming test. Aims: We aim at further characterising the phenotype found in the simple swimming test. Methods/techniques: We compared BACHD and wild-type rats in a Skinner box test that used multiple shifts. The boxes contained two cue lights with associated levers placed on either side of a food crib. One of the cue lights, randomly picked, would shine during trials. Rats were initially trained to respond either on the lever situated below the shining cue light, or on the lever of a particular side regardless of whether the cue light above it shined or not. Rats from both groups where then trained on a reversal of the original setting and finally on a shift to the setting of the other group. Results/outcome: All rats learnt the initial tasks at a similar rate. There was a trend indicating that BACHD rats were impaired during side reversal, while no differences were seen in the light reversal. BACHD rats were faster than wild-type rats at switching from side- to light-based strategy, while no differences where seen when the shift was made in the opposite direction. At certain steps, there were indications that BACHD rats were less motivated to work for the food reward. Conclusions: The results are not conclusive and it is unclear if BACHD rats are impaired during reversals and strategy shifts. There are however indications of other relevant phenotypes, such as a lowered or more sensitive motivational state.